Evaluation of the anti-inflammatory, analgesic and antipyretic activities of the natural polyphenol chlorogenic acid - Dos Santos, Michel David; Almeida, Maria Camila [UNESP]; Lopes, Norberto Peporine; De Souza, Glória Emília Petto (Pharmaceutical Society of Japan, 2006)
Phenolic compounds are numerous and ubiquitous in the plant kingdom, being particularly present in health-promoting foods. Epidemiological evidences suggest that the consumption of polyphenol-rich foods reduces the incidence of cancer, coronary heart disease and inflammation. Chlorogenic acid (CGA) is one of the most abundant polyphenol compounds in human diet. Data obtained from in vivo and in vitro experiments show that CGA mostly presents antioxidant and anti-carcinogenic activities. However, the effects of CGA on the inflammatory reaction and on the related pain and fever processes have been explored less so far. Therefore, this study was designed to evaluate the anti-inflammatory, antinociceptive and antipyretic activities of CGA in rats. In comparison to control, CGA at doses 50 and 100 mg/kg inhibited carrageenin-induced paw edema beginning at the 2nd hour of the experimental procedure. Furthermore, at doses 50 and 100 mg/kg CGA also inhibited the number of flinches in the late phase of formalin-induced pain test. Such activities may be derived from the inhibitory action of CGA in the peripheral synthesis/release of inflammatory mediators involved in these responses. On the other hand, even at the highest tested dose (200 mg/kg), CGA did not inhibit the febrile response induced by lipopolysaccharide (LPS) in rats. Additional experiments are necessary in order to clarify the true target for the anti-inflammatory and analgesic effects of CGA. © 2006 Pharmaceutical Society of Japan.
Keywords: Analgesic; Anti-inflammatory; Carrageenin; Chlorogenic acid; Formalin; Lipopolysaccharide (LPS); chlorogenic acid; lipopolysaccharide; polyphenol derivative; analgesic activity; animal experiment; animal model; antiinflammatory activity; antineoplastic activity; antinociception; antioxidant activity; antipyretic activity; controlled study; dose response; drug effect; drug inhibition; fever; inflammation; male; nonhuman; pain assessment; paw edema; rat; Administration, Oral; Analgesics; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Carrageenan; Chlorogenic Acid; Disease Models, Animal; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Edema; Fever; Flavonoids; Formaldehyde; Hindlimb; Inflammation; Lipopolysaccharides; Male; Molecular Structure; Pain; Phenols; Rats; Rats, Wistar; Time Factors